2017
DOI: 10.1021/acs.energyfuels.7b00364
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Interaction Forces between Clathrate Hydrate Particles in the Presence of a Water Bridge

Abstract: The agglomeration of hydrate particles is one of the main causes of hydrate accumulation or bedding in oil and gas pipelines. The unconverted water droplets in the system play a crucial role in hydrate particle agglomeration. In this study, a novel technique was developed to directly measure the interaction forces between cyclopentane hydrate particles with a water bridge between them using a micromechanical force apparatus. On the basis of the developed method, the interaction forces at different temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The weaker attractive force for the mixed oil case can be explained by the reduced interfacial tension from 48.7 , to 42.2 mN/m because of the presence of toluene. Besides, the interaction force could be greatly influenced by the new hydrate growth along the liquid bridge. ,, This sintering mechanism would play an important role when the contact time (i.e., time after hydrate bridge formation) lasts longer than 30 s . In this work, a short contact time of 7 s was adopted, allowing the assumption of negligible new hydrate growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weaker attractive force for the mixed oil case can be explained by the reduced interfacial tension from 48.7 , to 42.2 mN/m because of the presence of toluene. Besides, the interaction force could be greatly influenced by the new hydrate growth along the liquid bridge. ,, This sintering mechanism would play an important role when the contact time (i.e., time after hydrate bridge formation) lasts longer than 30 s . In this work, a short contact time of 7 s was adopted, allowing the assumption of negligible new hydrate growth.…”
Section: Resultsmentioning
confidence: 99%
“…All measured anti-adhesive force, interaction force, and delay of liquid bridge formation have clearly proven the remarkable influence of asphaltenes. However, it is also important to understand other effects of asphaltenes on the interaction between the water drop and hydrate particle, such as the corresponding change of hydrate equilibrium in mixed oil, , the subcooling effect with the addition of salts and the capillary tubing effect . It is also essential to investigate the combined effects of salts and other hydrocarbon species on the interaction force and hydrate formation rate in the future research.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements indicated that chemical or physical surface modifications alone may be insufficient to eliminate hydrate deposition risk. According to the research of Lee et al , and Liu et al, the coated water on the pipe wall significantly increased the adhesion force between hydrate particles and metal surfaces. Recently, using a custom-built high-pressure micromechanical force apparatus, Wang et al measured the adhesion forces between hydrate particles and CS surfaces at high pressures, and the effects of corrosion on the adhesion forces were analyzed .…”
Section: Introductionmentioning
confidence: 99%
“…Adhesive forces between clathrates and solid surfaces are a field of practical importance. Especially, this force causes a century-old problem of clathrate agglomeration and the consequence of pipeline blockage in the oil and gas industry. However, the origin of adhesion forces for clathrate surfaces is poorly understood.…”
Section: Introductionmentioning
confidence: 99%